The Future E-Living for Elderly: The Use of Remote Controlled Devices - Lam, Sanches; Chung, Winnie (International Journal of Online and Biomedical Engineering (iJOE), 2010)
Elderly populations are growing globally, the need for assistive technologies to facilitate ageing-in-place becomes more prominent for researchers and legislators. Understanding the use of remote controlled devices is crucial to optimize design and application strategies that may reduce caregiver burden, extend healthy ageing in place, and minimize demands on the health care system. This paper will establish strategies for assistance to the elderly in ageing-in-place for the future e-living environment. This research study is to explore attitudes, opinions, and preferences of older adults concerning the use of online technology to support and extend their ability to â??ageing in place.